Salt stress and hydroxyectoine enhance phosphate solubilisation and plant colonisation capacity of Kosakonia radicincitans - Cruz Barrera, Mauricio (J Adv Res, 2019)
Gram-negative bacterial endophytes have attracted research interest caused by their advantageous over epiphytic bacteria in plant nutrition and protection. However, research on these typically Gram-negative endophytes has deficiencies concerning the role of cultivation and pre-formulation strategies on further plant colonisation capabilities. Besides, the influence of cultivation conditions and osmotic stress within bacterial endophytes on their phosphate solubilising ability has not yet been addressed. By pre-conditioning cells with an osmoadaptation and a hydroxyectoine accumulation approach, this research aimed at enhancing the capability of the plant growth promoting bacterium Kosakonia radicincitans strain DSM 16656(T) to both solubilise phosphate and colonise plant seedlings. The results showed that halotolerant bacterial phenotypes increased the root-colonising capability by approximately 3-fold and presented growth-promoting effects in radish plants. Interestingly, findings also demonstrated that salt stress in the culture media along with the accumulation of hydroxyectoine led to an increase in the in vitro phosphate-solubilising ability by affecting the production of acid phosphatases, from 1.24 to 3.34 U mg(-1) for non-salt stressed cells and hydroxyectoine-added cells respectively. Thus, this approach provides a useful knowledge upon which the salt stress and compatible solutes in bacteria endophytes can confer phenotypic adaptations to support the eco-physiological performance concerning phosphate-solubilising abilities and endosphere establishment.